Acquired Downregulation of Donor‐Specific Antibody Production After ABO‐Incompatible Kidney Transplantation. Issue 1 (26th July 2016) - Tasaki, M.; Saito, K.; Nakagawa, Y.; Imai, N.; Ito, Y.; Aoki, T.; Kamimura, M.; Narita, I.; Tomita, Y.; Takahashi, K.
Abstract : The mechanism of long‐term B cell immunity against donor blood group antigens in recipients who undergo ABO‐incompatible (ABOi) living‐donor kidney transplantation (LKTx) is unknown. To address this question, we evaluated serial anti‐A and anti‐B antibody titers in 50 adult recipients. Donor‐specific antibody titers remained low (≤1:4) in 42 recipients (84%). However, antibodies against nondonor blood group antigens were continuously produced in recipients with blood type O. We stimulated recipients' peripheral blood mononuclear cells in vitro to investigate whether B cells produced antibodies against donor blood group antigens in the absence of graft adsorption in vivo . Antibodies in cell culture supernatant were measured using specific enzyme‐linked immunosorbent assays (ELISAs). Thirty‐five healthy volunteers and 57 recipients who underwent ABO‐compatible LKTx served as controls. Antibody production in vitro against donor blood group antigens by cells from ABOi LKTx patients was lower than in the control groups. Immunoglobulin deposits were undetectable in biopsies of grafts of eight recipients with low antibody titers (≤1:4) after ABOi LKTx. One patient with blood type A1 who received a second ABOi LKTx from a type B donor did not produce B‐specific antibodies. These findings suggest diminished donor‐specific antibody production function in the setting of adult ABOi LKTx. Abstract : In the setting of ABO‐incompatible kidney transplantation, recipients may acquire donor‐specific downregulation of antibody production against ABO blood group antigens.